The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16101845
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Audio-Visual Interactions on Psychological Responses of Young People in Urban Green Areas: A Case Study in Two Parks in China

Abstract: Audio-visual interactions in green spaces are important for mental health and wellbeing. However, the influence of audio-visual interactions on psychological responses is still less clear. This study introduced a new method, namely the audio-visual walk (AV-walk), to obtain data on the audio-visual context, audio-visual experiences, and psychological responses in two typical parks, namely Cloves Park and Music Park in Harbin, China. Some interesting results are as follows: First, based on Pearson’s correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…To some extent, the work by Payne and Bruce [8] also claims that the type of sounds heard and other aspects of a site experience are likely to be related to a non-linear relationship between sound levels and perceived restoration of an acoustic environment. Other contextual aspects might indeed play a role, such as audio-visual interactions in environmental perception, as suggested in the work by Zhang et al [9]. Cerwén [10] explores new autoethnographic approaches to propose possible actions, which are organized into three main categories (i.e., localization of functions, reduction of unwanted sounds, and introduction of wanted sounds) that designers can take into account when managing quiet areas in the urban realm.…”
Section: Rethinking Quiet Areas and Their Restorative Potential For Hmentioning
confidence: 99%
“…To some extent, the work by Payne and Bruce [8] also claims that the type of sounds heard and other aspects of a site experience are likely to be related to a non-linear relationship between sound levels and perceived restoration of an acoustic environment. Other contextual aspects might indeed play a role, such as audio-visual interactions in environmental perception, as suggested in the work by Zhang et al [9]. Cerwén [10] explores new autoethnographic approaches to propose possible actions, which are organized into three main categories (i.e., localization of functions, reduction of unwanted sounds, and introduction of wanted sounds) that designers can take into account when managing quiet areas in the urban realm.…”
Section: Rethinking Quiet Areas and Their Restorative Potential For Hmentioning
confidence: 99%
“…Human senses are not able to work independently [1,2,3,4,5,6,7,8,9,10,11,12]. Yang and Moon [13] investigated variation in acoustic, thermal, visual, and indoor environmental comfort, under the influence of multisensory interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory stimulation by the forest, such as the sound of leaves shaking in the wind, singing birds, and the sound of flowing streams, can contribute to psychophysical relaxation and stress recovery [ 102 , 103 , 104 ]. For example, Zhang et al [ 103 ] reported that the acoustic and visual comfort given in the green environment had a strong positive correlation with low depression and anxiety. In particular, acoustic comfort showed a more significant influence than visual comfort.…”
Section: Discussionmentioning
confidence: 99%